Traditional Games as A Learning Strategy to Develop Students' Self-Control - Mahfud, Mahfud; Susanto, Nugroho; Widyasari, Riztika; Firdaus, Fadli; Witasari, Rinesti (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Self destructive behavior and that of others can result from low self-esteem self-control ability or self-control in students. On the other hand, good self-control can influence student learning outcomes and achievements.Self control itself includes 3 aspects including behavioral control, cognitive control, and decision control.One way that can be done to develop students' self-control is with game strategies, one of which is traditional games, where traditional games are now rarely found.The purpose of this study was to conduct a literature review related to game strategies in developing students' self-control. This is a qualitative-library research. The researcher conducted research on the results of journal research related to traditional game strategies to develop students' self-control. Data and research data sources are in the form of ten studies with the theme of game strategies to develop students' self-control. Data sources were obtained from e-journals accessed from Google Scholar, ScienceDirect, and Elsevier. The sources sought were research results from 2020 to 2023. Data collection techniques used data collection techniques with the keywords game strategies and student self-control. Researchers collect data on research data obtained from the Google Scholar, Elsevier, and ScienceDirect with data analysis techniques using content analysis methods. Based on several research results it was found thatgame strategy can be used asmedium to developself control onstudentself-controlthis includesbehavioral control, cognitive control, and decision control.Based on the results of the research, it is hoped that teachers can continue to preserve traditional games which are now starting to be abandoned, as media used in learning.